The Influence of Business Cultures in Europe An Exploration of Central, Eastern, and Northern Economies (Palgrave Macmillan UK, 2018)
'Robert Crane's authors provide us with the kind of information we need. They do not limit themselves to present affairs, but also give us insight into the historical developments that helped to shape the present.' -Geert Hofstede This book explores the way that culture and societal values impact the economies of eight European countries, focussing on businesses and their organisation and management processes. With contributions from skilled authors that cover Central, Eastern and Northern Europe, and particularly Russia, Germany, and Scandinavia, this collection provides a broad understanding of how business is conducted within the different countries of peripheral Europe. The book seeks to examine the influence of culture on business, and more specifically the interaction between national and corporate cultures. It will be of great interest to researchers interested in international business, cross-cultural management, and business organisation.